(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rafi M, Septaningsih DA, Karomah AH, Lukman, Prajogo B, Amran MB, Rohman A. 2021. Inhibition of ?-glucosidase activity, metals content, and phytochemical profiling of Andrographis paniculata from different geographical origins based on FTIR and UHPLC-Q-Orbitrap HRMS metabolomics. Biodiversitas 22: 1535-1542. Ensuring consistency of quality, safety, and efficacy of herbal medicines from raw materials to finished products is important because of the variability in medicinal plants’ active components. One of the plants that have been used as an antidiabetic herbal medicine is A. paniculata. This study aims to determine ?-glucosidase inhibitory activity, the content of several metals, FTIR spectrum profile, and putative identification of A. paniculata metabolites using UHPLC-Q-Orbitrap HRMS from different geographical origin. We found that ethanol extract of A. paniculata gave higher inhibition of ?-glucosidase activity compared to water extract. Eight metals were determined using FAAS and FAES, and calcium showed the highest content in all A. paniculata samples. FTIR spectra of A. paniculata showed a similar profile and only differed in the absorbance. We detected the presence of OH, C=O, C=C aromatic, and C-O functional groups in A. paniculata extract. About 32 metabolites were putatively identified in A. paniculata, mainly from phenolic and diterpene lactones class compounds based on UHPLC-Q-Orbitrap HRMS. Using a combination of FTIR spectra and peak area from 32 identified peaks, we can clustered A. paniculata based on its geographical origin. Based on the result obtained, the geographical origin of A. paniculata affected the metals and metabolites composition and level, resulting in different levels of ?-glucosidase inhibitory activity.